Factors Influencing The Decision To Purchase An OPPO Mobile Phone At The Semaku Ponsel Manna Counter In South Bengkulu - Yesi Apriana; Ida Anggriani; Aji Sudarsono (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This research aims to determine the physical, social, personal and psychological factors on purchasing decisions at the Semaku Ponsel Manna Counter, South Bengkulu. The method in this research uses validity testing, reliability testing, multiple linear regression analysis, coefficient of determination and hypothesis testing. This type of research uses quantitative research. The number of samples in this study was 62 visitors who came to the Semaku Ponsel Manna Counter, South Bengkulu Regency, who were chosen randomly. The results of the multiple linear regression analysis are the equation: Y = 7.546 + 0.165 X1 + 0.313X2 + 0.167X3 + 0.210 The value of the coefficient of determination from the results of calculations using SPSS can be seen that the coefficient of determination value from R square is 0.672. This means that the value of cultural factors (X1), the value of social factors (X2), the value of personal factors (X3), and psychological factors (X4) influence purchasing decisions (Y) by 67.2% while the remaining 32.8% is influenced by other variables not examined in this research. The test results for the variables cultural factors (X1), social factors (X2), personal factors (X3) and psychological factors (X4) simultaneously have a significant influence on purchasing decisions at Semaku Ponsel Manna, South Bengkulu. This is proven by the significance value of 0.000 which is smaller than 0.05. So Ho is rejected and Ha is accepted. Thus, it can be concluded that these four variables together have a significant influence on cellphone purchasing decisions among consumers of Semaku Ponsel Manna, South Bengkulu.